Mass Spectrometry and Gas‐Phase Chemistry of Bismuth–Oxido Clusters. Issue 9 (17th June 2013) - Sattler, Dominik; Schlesinger, Maik; Mehring, Michael; Schalley, Christoph A.
Abstract The mass spectrometric characterisation of bismuth–oxido clusters is described together with tandem mass spectrometric experiments aimed at investigating their gas‐phase chemistry. Clusters with different ligand shells (nitrate, salicylates, and methacrylate) and different sizes (Bi6O8, Bi22O26, and Bi38O45) were selected for this study. The following aspects were addressed by (tandem) electrospray ionisation Fourier‐transform ion‐cyclotron‐resonance (ESI‐FTICR) mass spectrometry: 1) Electrospray ionisation was used successfully for the generation of intact cluster ions, but led to rather complicated distributions of charge states and solvent adducts. The cluster core remained intact. 2) Mass spectrometry was used to follow the cluster growth from Bi6O8 to Bi22O27 and finally Bi38O45 clusters. These experiments revealed that careful tuning of the conditions is required to avoid precipitates forming that hamper ESI ionisation. The stages of growth strongly depend on the experimental conditions. 3) Fragmentation experiments in the gas phase performed with the Bi22O27 clusters obtained in the growth experiments resulted in the preferential formation of Bi6O8 fragments and point to the particular stability of this cluster and its role in cluster growth. 4) Solution‐phase ligand‐exchange reactions on Bi22O26 salicylate clusters were qualitatively monitored by mass spectrometry, but were limited by the complicated ion series formed that led to overlapping isotope patterns. 5) A number of fragmentation reactions occurred within the ligand shell when the clusters surrounded by an organic ligand shell were subjected to infrared multiphoton dissociation experiments. 6) For the nitrate clusters, fragmentation within the core was observed yielding Bi6O8 fragments together with the corresponding clusters of reduced size.